Endotrophin levels in clinically-stable chronic obstructive pulmonary disease (Annals of Medical Research, 2021)
Aim: Chronic obstructive pulmonary disease (COPD) is characterized by chronic inflammation and permanent airflow limitations due to stenosis of the small airways. The role of the extracellular matrix (ECM) structure and its reshaping is gaining importance. Endotrophin is a division product formed during construction of type VI collagen. The aim of this study was to research the correlation between endotrophin and the stable COPD pathophysiology.Materials and Methods: The study included 90 clinically-stable COPD patients and 38 participants without COPD. The demographic data, respiratory function tests and endotrophin levels of patients were recorded and statistically evaluated.Results: Endotrophin levels were significantly high in COPD patients compared to healthy controls (p
Keywords: CRP; chronic obstructive pulmonary disease; endotrophin; extracellular matrix; inflammation